RETRACTED: Facies analysis and depositional environments of the Oligocene–Miocene Asmari Formation, Zagros Basin, Iran - Mohammad Sahraeyan (Geoscience Frontiers, 2014)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy). This article has been retracted at the request of the Editor-in-Chief. The article duplicates significant parts of three other articles without proper citations (Allahkarampour Dill, M., Seyrafian, A., Vaziri-Moghaddam, H., 2010. The Asmari Formation, north of the Gascharan (Dill anticline), southwest Iran: facies analysis, depositional environments and sequence stratigraphy, Carbonates Evaporites, 25, 145-160, http://dx.doi.org/10.1007/s13146-010-0021-6; Jamalian, M., Adabi, M.H., Moussavi, M.R., Sadeghi, A., Baghbani, D., Ariyafar, B., 2011. Facies characteristic and plaoenvironmental reconstruction of the Faliyan Formation, Lower Cretaceous, in the Kuh-e Siah area, Zagros basin, southern Iran. Facies 57, 101-122, http://dx.doi.org/10.1007/s10347-010-0231-3; Bahrami, M., Sahraeyan, M., Taherkhani, K., 2012, Microfacies and Sedimentary envrionments of Dalan Formation at Surmeh Mountain, Folded Zagros Zone, Southwestern Iran. International Journal of Basic and Applied Sciences 4, 380-389, http://dx.doi.org/10.14419/ijbas.v1i4.251). The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.